Exploring the Role of Digital Literacy and Grit on Teacher Performance: A Meta-Analysis - Wijaya Wijaya; Widodo Widodo; Hasbullah Hasbullah; Mohammad Yusoph P. Mapia (Jurnal Pendidikan Progresif, 2026)
This study aims to systematically examine the influence of digital literacy and grit on teacher performance through a quantitative meta-analysis approach. The study is grounded in the growing importance of digital competence and non-cognitive psychological traits as key determinants of teacher effectiveness in the era of rapid digital transformation and increasing educational demands. While numerous empirical studies have investigated these relationships, their findings remain fragmented and inconsistent across different contexts, thus necessitating a comprehensive synthesis. A total of 28 peer-reviewed empirical studies published between 2018 and 2025 were selected using strict inclusion criteria and analyzed using JASP. A random-effects model was employed to estimate the pooled effect sizes, as the included studies varied in design, sample characteristics, and educational settings. Effect sizes were calculated using correlation coefficients (r), converted to Fisher’s Z values, and subsequently transformed back to r for interpretation. Heterogeneity among studies was assessed using the Q test and I² statistic, and potential publication bias was examined using forest and funnel plots. The meta-analysis results indicate that digital literacy is positively and statistically significantly related to teacher performance, yielding a pooled effect size of r = 0.502 (p < 0.001). Similarly, grit significantly influences teacher performance, with an effect size of r = 0.503 (p < 0.001). The I² values for both variables were 0%, indicating no substantial heterogeneity and suggesting that the findings are highly consistent and generalizable across studies. Visual inspection of forest and funnel plots further confirmed the absence of publication bias. In conclusion, this meta-analysis provides robust empirical evidence that both digital literacy and grit play crucial and complementary roles in enhancing teacher performance. These findings highlight the importance of integrating digital competency development and perseverance-oriented character education into teacher professional development programs and educational policy frameworks to promote sustainable improvements in teaching quality. Keywords: digital literacy, grit, teacher performance, meta-analysis.